The Use of Sentinel-2A Images to Estimate Potential Flood Risk With A Multi-Index Approach in The Mempawah Watershed - Ajun Purwanto; Paiman Paiman; Agus Sudiro (Department of Geography Education, University of Jember, 2023)
Natural disasters in Indonesia have become an annual cycle, an example is flooding. This study aims to determine the flood risk potential in the Mempawah watershed and the places likely to be flooded. The method used was a survey and interpretation of secondary data from topographic maps, Sentinel-2A images, and Digital Elevation Model images. Furthermore, the secondary data analysis used includes the Standardized Precipitation Index (SPI), Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), Soil Adjusted Vegetation Index (SAVI), and Inverse Distance Weighted (IDW). The result showed that the Mempawah watershed has high, medium, and low flood risk potential. Areas with high flood potential have an area of 1,511,967 ha, those with medium potential were 2,606,778 ha, and the places with low potential were 12,644,034 ha. The changes in class user's accuracy results reached 90.909%, while those with no change were 83.333%. It was also discovered that when the satellite analysis was > 70%, it was regarded as good. This means that the accuracy of the interpretation results and flood change detection approach was also good.